Evaluation of knowledge, attitude and practice of endodontic postgraduates towards preference of surgical vs non-surgical management of large periapical lesion - A survey (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Periapical lesion results from serious inflammatory response to microorganisms around the tooth root and the root canal. The most commonly involved site is maxillary anterior teeth. Patients encounter pain, discomfort or sensitivity to hot or cold beverages depending upon chronicity of the lesion. Aim of this study is to evaluate knowledge, attitude and practice of endodontic postgraduates towards preference of surgical vs non surgical management of large periapical lesions. Materials and methods: A cross sectional study was done among endodontic post graduates. The questionnaire consisted of 10 questions which were predominantly close ended. Survey results were validated using SPSS software version (22.0) and the data was collected according to respondents. Results: In this study 56.9% very often treat a periapical lesion, 36.7% treat sometimes and remaining 6.4% treat rarely. 69.7% of the respondents preferred non surgical treatment for periapical lesion and remaining 30.3% preferred surgical treatment. The Chi square test was performed and the p value = 0.465 - was insignificant.Conclusion: In this study we may conclude that the endodontic postgraduates had adequate knowledge and attitude towards preference of surgical vs non surgical management of large periapical lesions.